(untitled) (Nigerian Journal of Physiological Sciences, 2025)
Hypertension is one of the major risk factors for cardiovascular diseases. It has become a significant public health concern in both developed and developing countries. In this study we evaluated the ameliorative effect of methanol bark extract of Persea americana (PA) on L-NAME-induced hypertension and its attendant cardiac and renal complications. Sixty rats were divided into six groups. Group A was the negative control and received distilled water throughout the study. Group B received a daily repetitive dose of L-NAME alone at 40 mg/kg for 21 days. Groups C, D and E received a daily repetitive dose of L-NAME at 40 mg/kg and extract at 100 mg/kg, 200 mg/kg and 400 mg/kg, respectively, for 21 days. Group F received a daily repetitive dose of L-NAME at 40 mg/kg and lisinopril at 10 mg/kg for 21 days. The results showed that L-NAME significantly elevated blood pressure, markers of renal damage, oxidative stress, and expression of KIM-1, NRF2, NF-KB and CTnI, while it decreased both enzymatic and non-enzymatic antioxidant parameters. The extract and lisinopril, however, ameliorated these effects in the rat model. These findings showed that the bark extract of PA may play a role in reducing oxidative stress, inflammation, cardio-renal organ damage and blood pressure levels in hypertension, possibly through free radical scavenging, antioxidant system potentiation, NF-ƙβ/NRF2/KIM-1/CTnI signaling pathways. Keywords: Persea americana bark extract, hypertension, oxidative stress, antioxidant, L-NAME, lisinopril